POTRET NELAYAN NASIONAL DALAM PUSARAN KONSTITUSI - Abustan (JURNAL RISET INDRAGIRI, 2024)
The constitutional mandate emphasizes that everyone has the right to work and a decent life. This includes people who work as traditional fishermen in rural areas or on the coast. Juridically, referring to Article 1 number 2 of Law Number 1 of 2014 concerning amendments to Law Number 27 of 2007 concerning the management of Coastal Areas and small-scale areas, and defining traditional fishing as one of the jobs of citizens in coastal areas . In this regard, the government as the highest authority in the region basically has the obligation to regulate order. However, these arrangements should not conflict with the interests of coastal environmental management and society. For this reason, Indonesia is a rule of law country where the constitution is the philosophical basis of national law. So, existing construction (building) regulations must not conflict with the constitution as the supreme law of the land. The aim of the research is to find out the role and duties of local governments in regulating government policies and regulations, especially improving the welfare of traditional fishermen. This research is empirical research, using a sociological juridical approach. The reality of the conditions that exist in the lives of traditional fishermen is that various advances have been found, both in the infrastructure sector and fishermen's education, including advocacy and fishermen's understanding of regulations that provide protection for fishermen's fundamental rights.